2017
DOI: 10.1128/aac.00385-17
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Dissemination of OXA-232 Carbapenemase-Producing Klebsiella pneumoniae in Neonates

Abstract: Five OXA-232 carbapenemase-producing Klebsiella pneumoniae isolates, belonging to the pandemic clone sequence type 15 (ST15), were isolated from neonates and coproduced bla CTX-M-15 and bla SHV-1 genes. All isolates were resistant to ertapenem (MICs of Ͼ32 g/ml) and meropenem (MICs of 4 to 8 g/ml) and susceptible or intermediate to imipenem (MICs of 1 to 2 g/ml). The bla OXA-232 gene was located on a ColE-type transformable plasmid of 6,141 bp. To the best of our knowledge, this is the first report of OXA-232 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 18 publications
(14 reference statements)
3
67
0
1
Order By: Relevance
“…Strain E109-1 harbored a 5,339,953-bp chromosome and 177,872-, 135,859-, 128,536-, and ϳ78-kb plasmids, as well as six small plasmids (Ͼ10 kb). bla OXA-232 was located in a 6,141-bp ColKP3-type plasmid designated pE109-1-OXA, which was recovered from all 10 isolates and was 99% identical to the previously reported 6.1-kb bla OXA-232 -bearing plasmid pkNICU5 isolated from a K. pneumoniae strain in China, with 100% coverage (6). The plasmid comprised nine open reading frames (ORFs), including repA, mobA, mobB, mobD, ΔmobC, ΔISEcp1, bla OXA-232 , ΔlysR, and ΔereA, and was not transferable to Escherichia coli EC600 (rifampin resistant) via conjugation (6,11).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Strain E109-1 harbored a 5,339,953-bp chromosome and 177,872-, 135,859-, 128,536-, and ϳ78-kb plasmids, as well as six small plasmids (Ͼ10 kb). bla OXA-232 was located in a 6,141-bp ColKP3-type plasmid designated pE109-1-OXA, which was recovered from all 10 isolates and was 99% identical to the previously reported 6.1-kb bla OXA-232 -bearing plasmid pkNICU5 isolated from a K. pneumoniae strain in China, with 100% coverage (6). The plasmid comprised nine open reading frames (ORFs), including repA, mobA, mobB, mobD, ΔmobC, ΔISEcp1, bla OXA-232 , ΔlysR, and ΔereA, and was not transferable to Escherichia coli EC600 (rifampin resistant) via conjugation (6,11).…”
mentioning
confidence: 53%
“…bla OXA-232 was located in a 6,141-bp ColKP3-type plasmid designated pE109-1-OXA, which was recovered from all 10 isolates and was 99% identical to the previously reported 6.1-kb bla OXA-232 -bearing plasmid pkNICU5 isolated from a K. pneumoniae strain in China, with 100% coverage (6). The plasmid comprised nine open reading frames (ORFs), including repA, mobA, mobB, mobD, ΔmobC, ΔISEcp1, bla OXA-232 , ΔlysR, and ΔereA, and was not transferable to Escherichia coli EC600 (rifampin resistant) via conjugation (6,11). All strains exhibited similar drug resistance profiles, including phenotypic resistance to cefmetazole, ceftazidime, cefotaxime, piperacillin-tazobactam, cefoperazone-sulbactam, cefepime, ciprofloxacin, amikacin, and aztreonam, but remained susceptible to ceftazidime-avibactam, tigecycline, and polymyxin B.…”
mentioning
confidence: 53%
“…OXA232Kp has been reported in eastern China. All these OXA232Kp isolates belong to ST15 and carry a 6.1-kp ColKP3 plasmid bearing the bla OXA-232 gene [21][22][23]. In this study, we reported a nosocomial outbreak of OXA232Kp in a teaching hospital in Shanghai involved with 61 patients.…”
Section: Introductionmentioning
confidence: 81%
“…2) and appeared to be clonal. At the same time, several outbreak caused by OXA232Kp have been identified in the same area [21][22][23]. Recently, an outbreak of OXA-48-producing K. pneumoniae involving 34 patients at a respiratory ICU has been reported [7].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, several CRE strains were negative for both bla KPC and bla NDM , and we speculate that these strains may produce the AmpC ␤-lactamase, combined with the increased expression or a deficiency of outer membrane protein, or may produce other carbapenems besides those of the NDM type and KPC type, another important resistance mechanism of CRE. For example, we have reported the clonal spread of the OXA-232 carbapenemase before, and strains positive for the OXA-232 carbapenemase were also susceptible to ceftazidime-avibactam (15). Porin mutations and the increased expression of KPC-3 have been reported to be one of the mechanisms related to resistance to ceftazidime-avibactam in K. pneumoniae (16).…”
Section: Discussionmentioning
confidence: 99%